Texture dependent strain rate sensitivity of ultrafine-grained aluminum films. (15th March 2016) - Izadi, Ehsan; Rajagopalan, Jagannathan
Abstract: We investigated the strain rate sensitivity (SRS) of freestanding ultrafine-grained aluminum films with similar thickness (~ 240 nm) and mean grain size (~ 275 nm) but highly dissimilar texture. For (110) textured bicrystalline films, flow stress increased by 14% ( m  = 0.017) as the strain rate was varied from ~ 7 × 10 − 6 /s to 5 × 10 − 3 /s. In contrast, for non-textured films the flow stress increased by more than 90% ( m  = 0.103) over a similar strain rate range. The drastic difference in SRS can be explained by texture-induced changes in deformation mechanisms of the films, as revealed by in situ TEM straining experiments. Graphical abstract: